Agency and the roles of Southern Jordanian Bedouin women on pilgrimage and visiting holy sites - Päivi Miettunen (Approaching Religion, 2018)
In the Islamic world, numerous shrines shape and define its spiritual landscapes. While some of the shrines are tombs and memorials of major religious and historical figures, a majority of the sites are dedicated to ancestors of the local families and tribes. They function as centres of the religious community, but they also provide a secluded location for private spiritual visits and individual prayers. Women have participated in public rituals also, but it is in the private religious sphere that the women have created a space for independent religious action, connected, and yet separate from their mundane roles.